2020
DOI: 10.1002/1873-3468.13983
|View full text |Cite
|
Sign up to set email alerts
|

A twist in the ABC: regulation of ABC transporter trafficking and transport by FK506‐binding proteins

Abstract: Post‐transcriptional regulation of ATP‐binding cassette (ABC) proteins has been so far shown to encompass protein phosphorylation, maturation, and ubiquitination. Yet, recent accumulating evidence implicates FK506‐binding proteins (FKBPs), a type of peptidylprolyl cis–trans isomerase (PPIase) proteins, in ABC transporter regulation. In this perspective article, we summarize current knowledge on ABC transporter regulation by FKBPs, which seems to be conserved over kingdoms and ABC subfamilies. We uncover striki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 87 publications
(171 reference statements)
1
14
0
Order By: Relevance
“…4A), can have such a drastic effect on ABCG36 substrate specificity. One explanation might be that these regions function in analogy to the regulatory linker or R-domains connecting the two halves of full-size transporters of ABCBs or CFTR/ABCC7, respectively, and where phosphorylation is thought to add negative charges that by means of conformational changes altering ABC functional capacities (Aryal et al, 2015; Gadsby et al, 2006; Geisler and Hegedus, 2020). This model was very recently supported by cryo-EM imaging of the ABCC, yeast cadmium factor (YCF1), showing that the YCF1 R-domain associates upon phosphorylation with NBD1 altering directly its ATPase activity (Khandelwal et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…4A), can have such a drastic effect on ABCG36 substrate specificity. One explanation might be that these regions function in analogy to the regulatory linker or R-domains connecting the two halves of full-size transporters of ABCBs or CFTR/ABCC7, respectively, and where phosphorylation is thought to add negative charges that by means of conformational changes altering ABC functional capacities (Aryal et al, 2015; Gadsby et al, 2006; Geisler and Hegedus, 2020). This model was very recently supported by cryo-EM imaging of the ABCC, yeast cadmium factor (YCF1), showing that the YCF1 R-domain associates upon phosphorylation with NBD1 altering directly its ATPase activity (Khandelwal et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a gene duplication event in the ABC transporter family (Ogasawara et al, 2020) hindered their identification in classical genetic screens (Zhang et al, 2018). In between, based on the identification of a signature D/E-P motif for auxin transporting ABCBs (ATAs) it was suggested that 11 of the 22 full-size ABCBs are ATAs (Geisler and Hegedus, 2020;Hao et al, 2020). In between, functional redundancy between similar ATA isoforms could be solved by using clade-specific gene silencing (Zhang et al, 2018).…”
Section: Auxin Transportersmentioning
confidence: 99%
“…As a result, abcb1 abcb19 plants resemble the twd1 mutant and show similar PAT defects (Geisler et al, 2003; see Figure 1). However, auxin-transporting ABCBs (ATAs) contain an essential proline as part of a diagnostic D/E-P motif in their C-terminal nucleotidebinding folds that is essential for auxin transport but not for trafficking (Geisler and Hegedus, 2020;Hao et al, 2020). Thus, TWD1 might have a dual role in ABCB activation and secretion, respectively, which is an analogy to human FKBP38 (Geisler and Hegedus, 2020).…”
Section: Auxin Transporter Regulationmentioning
confidence: 99%
“…However, translation of biochemical findings to clinically relevant concepts is not always straightforward. Structural alterations may not only result in defects of transporter or channel activity, but also result in improper folding, derailed trafficking, and degradation [27]. The clinical relevance of these alterations in drug metabolism, cancer multidrug resistance, and impaired physiology is also discussed [28].…”
Section: The Role Of Abc Transporters In Health and Diseasementioning
confidence: 99%